Use of Placuna placenta Shells as Green Adsorbent for Pb(II) Ions Sequestration from Aqueous Solution - Eko Prasetyo Kuncoro; Claudia Deborah Pretty Matondang; Muchlis Fajar Hidayat; Handoko Darmokoesoemo (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
Heavy metal treatment is crucial to mitigate these elements' adverse environmental impacts. Among various remediation methods, adsorption stands out due to its simplicity and high efficiency. In this context, Placuna placenta shell, a biowaste, has been explored for its potential in treating wastewater contaminated with Pb(II) ions. This research was designed to assess the Placuna placenta shell's proficiency in removing Pb(II) ions from aqueous solutions. The study involved two main components: an adsorption test to evaluate the heavy metal removal capability of the Placuna placenta shel and a comprehensive characterization of the shell-based adsorbent. The adsorption experiments were conducted using a batch system, where variables such as pH levels and contact time were meticulously altered to determine their effect on the adsorption efficiency. Concurrently, the adsorbent underwent thorough characterization through Fourier-Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD) analysis. The experimental findings indicated that the optimal conditions for maximum Pb(II) ion removal were achieved at a pH of 7 and a contact time of 120 minutes. The FTIR analysis of the adsorbent revealed the presence of calcium carbonate (CaCO3), a finding further substantiated by the XRD analysis results. Additionally, SEM imaging provided visual evidence of metal ion deposition on the aggregates of the adsorbent. The study demonstrated that the Placuna placenta shell exhibits promising qualities as an adsorbent for removing heavy metals from contaminated water sources. This finding highlights the potential of utilizing biowaste in environmental remediation and offers a sustainable approach to addressing heavy metal pollution.